Psychological stress responses to a live performance by professional flamenco dancers - de las Heras Fernández, Rosa; Mendoza, Guillermo; Jiménez, Manuel (PeerJ, 2023)
Dance is a high demanding discipline that involves physiological and psychological pressures. The pressure increases when dancers perform in front of an audience that, on a physiological level, can generate hormonal responses similar to those of an athlete before a competition for social status. Low levels of testosterone (T) and high levels of cortisol (C) are related to a decrease in performance and an increase in the risk of injury. Therefore, this study sets out to analyse hormone response patterns in professional flamenco dance performances depending on whether the performances are completed successfully and whether there are differences by sex and professional category. Saliva specimens (2-5 ml) were taken from the participants before and after the performance. Samples were immunoassayed by duplicate to analyze momentary fluctuations in two hormones regularly used in studies with professional athletes. The results showed significant differences in solo dancers' T responses before and after the performance (p < 0.01), suggesting that the dancing role in the show (soloist or corps the ballet) and responsibility over the performance were important modulators to the hormone responses observed.
Keywords: cortisol; performance; professional dance; stress; testosterone; JCR; Scopus